Single-Center Long-Term Analysis of Combined Liver-Lung Transplant Outcomes. Issue 5 (May 2018) - Freischlag, Kyle William; Messina, Julia; Ezekian, Brian; Mulvihill, Michael S.; Barbas, Andrew; Berg, Carl; Sudan, Debra; Reynolds, John; Hartwig, Matthew; Knechtle, Stuart
Abstract : Background: Combined lung-liver transplantation (LLT) applies 2 technically challenging transplants in 1 patient with severe 2-organ failure. Methods: Institutional medical records and United Network for Organ Sharing database were queried for patients at our institution that underwent LLT from 2000 to 2016. Results: Twelve LLTs were performed from 2000 to 2016 including 9 male and 3 female recipients with a median age of 28.36 years. Indications for lung transplantation were cystic fibrosis (8), idiopathic pulmonary fibrosis (3), and pulmonary fibrosis secondary to hepatopulmonary syndrome (1). Indications for liver transplantation were cystic fibrosis (8), alcoholic cirrhosis (1), idiopathic cirrhosis (2), and alpha-1 antitrypsin deficiency (1). Median forced expiratory volume in 1 second at transplant was 27.8% (±20.38%), and mean Model for End-Stage Liver Disease was 10.5 (±4.68). Median hospital stay was 44.5 days. Seventy-five percent of recipients had 1+ new infection during their transplant hospitalization. Patients experienced 0.68 incidences of acute rejection per year with a 41.7% (95% confidence interval, 21.3%-81.4%) probability of freedom from rejection in the first-year. Patient survival was 100% at 30 days, 91.6% at 1 year, and 71.3% at 3 years. At the time of analysis, 7 of 12 patients were alive, of whom 3 survived over 8 years post-LLT. Causes of death were primary liver graft failure (1), bronchiolitis obliterans syndrome (2), and solid tumor malignancies (2). Conclusions: Our results indicate that LLT is associated with comparable survival to other LLT series and provides a granular assessment of infectious and rejection rates in this rare population.